A study of causal dynamics in crude oil prices in India. (2017) - Choudhary, Nidhi; Nair, Girish; Purohit, Harsh
The existing literature indicates that there have been numerous studies which have been done on causal dynamics of crude oil prices in India. However, these studies have failed to take into consideration the structural break in the statistics or the property of non-linearity. The present study is an important step in this direction. It seeks to bridge this research gap.